Price-based Demand-side Management Model for Industrial and Large Electricity Consumers - Dzyuba, Anatolyy; Solovyeva, Irina (International Journal of Energy Economics and Policy, 2020)
This article discusses a price-based demand-side management model for industrial and large power consumers. We have analyzed various factors affecting the improvement of energy efficiency on a national scale as well as at the level of select enterprises and large electricity consumers and have concluded that demand-side management is one the key areas of increasing energy efficiency, with the price-based consumption as its core element. Using the Russian electricity market as a model example, this article investigates the formation of all cost components of the ultimate power price – electricity, capacity and transmission services. Based on the results of the power cost component analysis, the article concludes that the price-based demand-side management can be applied to all price components and identifies areas and hours for optimal demand-side management in order to minimize the purchase price of electricity, while maintaining the aggregate demand. Based on the identified specifics, we have developed a price-based demand-side management model for industrial and large electricity consumers, taking into account the factors that limit the required management of the demand. The suggested model can be adapted for retail and wholesale electricity customers alike. Given that the Russian electricity market is largely similar to other power markets, such as Nord Pool, EPEX, Powernext, PJM, New England ISO, etc., the suggested management methods can be adapted for application in other countries. The article also discusses a communication strategy for the suggested model. The results of this research have high theoretical and practical importance and can be used in power purchase-related activities of industrial and other large consumers in any country where the electricity is priced according to market principles. Keywords: demand-side management of electricity, price-dependent consumption, energy costs, operational efficiency, energy efficiency, production scheduling JEL Classifications: Q43, P18, L94 DOI: https://doi.org/10.32479/ijeep.8982